2022
DOI: 10.3389/fped.2022.828300
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Congenital Heart Disease in Chinese Children With Different Birth Weights and Its Relationship to the Neonatal Birth Weight

Abstract: ObjectiveThis study aimed to examine the prevalence and the related risk factors of congenital heart disease (CHD) in children with different birth weights in China and the relationship between the subtypes of CHD and birth weight (BW).MethodsThis study conducted a cross-sectional survey on the data collected in the children’s congenital heart disease database (CHDD) established in China. This database contained data from one Grade A, Level III Children’s Public Hospital in Zhengzhou, Henan. The study included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In another study from China (Zhengzhou, Henan), the overall prevalence of CCDs was 8.44 per 1000 live births during 2014 to 2020. 147…”
Section: Congenital Cardiovascular Defects and Kawasaki Diseasementioning
confidence: 99%
“…In another study from China (Zhengzhou, Henan), the overall prevalence of CCDs was 8.44 per 1000 live births during 2014 to 2020. 147…”
Section: Congenital Cardiovascular Defects and Kawasaki Diseasementioning
confidence: 99%
“…4 LBW is strongly associated with childhood mortality and longterm health and can lead to diseases associated with low immune function, poor growth, cognitive impairment, late-stage centripetal obesity, cardiovascular disease and type 2 diabetes. 5 High rates of consanguinity, prematurity, increased number of older maternal pregnancies and lifestyle changes are significant factors associated with increased LBW rates. 6 MAC is a newborn with a BW >4000 g within 1 hour of birth.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%
“…CHD is one of the most critical risk factors for children's death, and most CHD-related deaths occur in low-and middle-income countries (18), which significantly burdens these countries. Previous studies have shown that CHDs increased the risk of adverse pregnancy outcomes, such as preterm birth, fetal brain damage and neonatal death (6,(19)(20)(21)(22)(23)(24)(25). And many studies regarded CHDs as adverse pregnancy outcomes (12,13).…”
Section: Introductionmentioning
confidence: 99%